2017
DOI: 10.1007/s11664-017-5784-2
|View full text |Cite
|
Sign up to set email alerts
|

Phytosynthesis of Silver Nanoparticles Using Myrtus communis L. Leaf Extract and Investigation of Bactericidal Activity

Abstract: Silver nanoparticles have been synthesized using only Myrtus communis L. leaf extract by a facile procedure without other reagents. The extract played the roles of both reducing and capping agent. The nanoparticles were characterized using field-emission scanning microscopy, and remained stable for at least 3 weeks. Antibacterial activity of the nanoparticles was evaluated toward Escherichia coli, Bacillus subtilis, Pseudomonas aeruginosa, Staphylococcus aureus, methicillin-resistant Staphylococcus aureus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…MIC value of synthesized aqueous silver nanoparticles against MRSA was 12.5 mg/mL, for E. coli -25 mg/mL in comparison to vancomycin -3 mg/ mL and gentamicin -6 mg/mL (Table 2). Ajdari et al [24] reported MIC value of E. coli 24.5 mg/mL and of MRSA -16.3 mg/mL against silver nanoparticles from M. communis leaf extract which coincided with our results. MBC was observed to be 25 mg/mL and 50 mg/ mL respectively for MRSA and E. coli in reference to 6 mg/mL for vancomycin and 12 mg/mL for gentamicin which were lower values obtained for our study as compared to Ajdari et al [24].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…MIC value of synthesized aqueous silver nanoparticles against MRSA was 12.5 mg/mL, for E. coli -25 mg/mL in comparison to vancomycin -3 mg/ mL and gentamicin -6 mg/mL (Table 2). Ajdari et al [24] reported MIC value of E. coli 24.5 mg/mL and of MRSA -16.3 mg/mL against silver nanoparticles from M. communis leaf extract which coincided with our results. MBC was observed to be 25 mg/mL and 50 mg/ mL respectively for MRSA and E. coli in reference to 6 mg/mL for vancomycin and 12 mg/mL for gentamicin which were lower values obtained for our study as compared to Ajdari et al [24].…”
Section: Resultssupporting
confidence: 92%
“…(A)) and E. coli (Figure5(B)) with respect to plant extracts. Recent study on Buffer extraction of M. communis showed strong sensitivity against Gram-positive bacteria[24].…”
mentioning
confidence: 99%
“…Its sweet components are stevioside, steviol bioside, ribodiazide and dalcoside [27]. Recent investigations have shown that this plant has the ability to prepare in a fast and non-toxic way chemically stable iron oxide, zinc oxide and zinc sulfide nanoparticles [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials are developed due to exhibition of novel characteristics arising from their size-dependent features, and widely used in medical diagnoses and therapies [8][9][10]. These materials have a usage in biological and medical applications such as labeling of biomolecules [11], drug and gene delivery [12][13][14], rapid and sensitive microbial detections [15,16], antimicrobial materials [10,[17][18][19], detection and recognition of DNA and proteins [20][21][22], probing of intrinsic DNA structure [23], biologic substitutes and regenerative medicine [24], hyperthermia [25], separation of specific cell types [26] and MRI contrast agents [27]. Photothermal agents employed in PTT should absorb NIR light, while they possess photostability with no cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%